Fruit and Vegetable Intake Differences between Body Mass Index (BMI) Classes Among College-Aged Young Adults. (14th June 2022) - Parker, Kelly; Rhee, Yeong
Abstract: Objectives: Obesity continues to be a concern in the United States. A high-fiber diet, rich in fruits and vegetables, can reduce the risk of obesity and many chronic conditions. However, most Americans consume fewer than the 5–9 servings of fruits and vegetables recommended per day by the Dietary Guidelines for Americans. Health interventions in young adults are likely to produce healthful habits that last a lifetime. This study examined whether fruit and vegetable intake differed between healthy weight and overweight participants in a sample of college-aged young adults. Methods: A survey, including a food frequency questionnaire and self-reported height and weight, measured average daily fruit and vegetable intake in a sample of college-aged young adults (N = 274). Body mass index (BMI) was calculated, and independent t-test was used to measure differences in fruit and vegetable intake based on BMI classification (healthy weight: BMI 18.5–24.9 kg/m 2 [n = 152] vs overweight: BMI ≥ 25 kg/m 2 [n = 109]). Underweight participants (BMI < 18.5 kg/m 2 [n = 13]) were excluded from analysis. Results: Fruit intake differed based on BMI classification ( p  = 0.01). Participants with a healthy weight reported consuming slightly more fruit than overweight participants (1.44 ± 1.66 < vs 1.01 ± 1.04 servings/day). However, there was no significant difference in vegetable intake between healthy weight and overweight participants ( p  = 0.60, 1.85 ± 1.52 vs 1.76 ± 1.27 servings/day). Conclusions: Fiber and water in fruits may contribute to feelings of fullness, decreased overeating, and a healthier weight. While fruit and vegetable consumption can contribute to a healthy weight and other benefits, this study shows that fruit and vegetable consumption are not the sole drivers of a healthy weight. It also suggests the need for education about caloric balance, portion control, and physical activity, which are contributors to weight and BMI status. Funding Sources: Not applicable.